Postnatal development of nitric oxide synthase-expressing neurones in the enteric nervous system of the goat - Zixu Wang; Yaoxing Chen; Liujun Jia; Yunfang Liu (Italian Journal of Animal Science, 2010)
The morphology and distribution of nitric oxide synthase (NOS)-expressing neurons in the myenteric plexus of small intestine of goat at different ages (2 weeks, and 2, 4, 6 and 12 months) were studied by using nicotinamide adenine dinucleotide phosphate-diaphorase (NADPH-d) histochemistry, which could stain NOS-expressing neurons as immunohistochemistry. The results showed that the NADPH-d neurons and their fibres formed a clear tertiary meshwork structure in the myenteric plexus. The shapes of stained neurons were diverse, and many neurons gathered to form numerous ganglia in variable size. During development, the density of NADPH-d neurons in the myenteric plexus of goat small intestine decreased from 27.07/mm2 at 2 weeks to 16.18/mm2 at 12 months. The total number calculated referred to the total serosal surface of small intestine, however, increased from 1.86×106 at 2 weeks to 5.84×106 at 6 months, before decreasing to 4.41×106 at 12 months. At different ages, the density of NADPH-d neurons was lowest, but the total number was highest, in the jejunum with respect to duodenum and ileum. The mean area of the perikaryon or nucleus was enlarged at first and then diminished as the goats growing. The nuclear:cytoplasmic size ratio in NADPH-d neurons at 2 weeks was much higher than that at 2, 4, 6 or 12 months (P<0.05), while no differences could be found among different ages (P>0.05).